The Intersection of Intellectual Property Law and Business Strategy: Leveraging Legal Frameworks and Analytics to Drive Innovation and Market Competitiveness - Adeyinka Lawal,; Bisayo Oluwatosin Otokiti,; Sibongile Gobile,; Adeola Okesiji,; Odunayo Oyasiji, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This paper explores the intersection of intellectual property law and business strategy, highlighting the critical role that intellectual property (IP) plays in fostering innovation and enhancing competitive advantage in today’s dynamic business environment. The study outlines the strategic importance of various forms of IP—such as patents, trademarks, copyrights, and trade secrets—and their implications for business growth. It delves into the legal frameworks governing IP at national and international levels, identifying the challenges and opportunities businesses face in navigating these complexities. Furthermore, integrating data analytics into IP management illustrates how organizations can leverage analytical tools to assess IP portfolios, monitor infringements, and forecast market trends. The paper concludes with insights into the implications for future business practices and provides recommendations for areas of further research. Overall, this comprehensive analysis underscores the necessity for businesses to effectively manage their intellectual assets in order to achieve sustainable success in an increasingly competitive landscape.
Keywords: Intellectual Property; Business Strategy; Data Analytics; Innovation; Legal Frameworks; Competitive Advantage